Coloniality, the Bane of Peace and Development in Africa (Journal of Governance and Development (JGD), 2019)
The struggle against colonialism and the attainment of independence in Africa raised hopes that Africa would industrialise and develop alongside other parts of the global community. This has however not come to pass as most parts of the Global North are in the Fourth Industrial Revolution Era while Africa remains mired in violent conﬂict, poverty, ethnicity, dictatorship and corruption that are retarding peace, security and development despite the fall of formal empire. This paper examines the dilemma of peace and security in Africa. Many conﬂict theorists and peace builders in the South advance neo-colonialism, neo-liberalism and globalisation as sources of conﬂict and factors blocking peace on the African continent. The paper, apply a qualitative study employing decolonial analysis and drawing data from relevant documents argues that the continuation of colonial patterns of domination in the realms of power, knowledge and being in spite of the end of juridical – political domination is the raison d’etre for the seemingly unending conﬂicts that have engulfed the African continent to the detriment of peace and development. The paper reveals how coloniality has produced a ‘postcolonial’ leadership that has continued to practice politics in a violent, repressive, corrupt and unaccountable manner informed by colonial logic that breeds inimical practices such as racism, tribalism, regionalism and patriarchy. Finally, the paper advocates for decoloniality for peace and development to be achieved in Africa.